A time-use perspective of out-of-home activity participation by older people in Hong Kong. Issue 1 (2nd January 2022) - He, Sylvia Y.; Chakrabarti, Sandip; Cheung, Yannie H.Y.
ABSTRACT: Promoting active aging has emerged as a key objective of urban planning and policymaking globally. Our study aims to provide new insights from a time-use perspective. In this paper, we use Hong Kong as a case study to investigate how people aged 60 and older allocate their time in various out-of-home activities. We analyse how personal and household characteristics affect the duration of out-of-home activities among older adults using two decennial time-use surveys. We focus on the influence of employment status and age because of policy relevance, particularly since the Hong Kong Government is considering extending the retirement age from 60 to 65. Comparison of time-use and activity participation between 2002 and 2013 suggests that employment status is positively associated with the duration of out-of-home activities and travel in both cross-sections; it also explains change over time. Findings also underscore the role of gender, age, education, type of housing, tenure of accommodation, household size, and income in determining older people's activity–travel patterns. Our study shows that government policies to increase the share of employed people in the 60-years-and-older cohort and changes in the sociodemographic makeup of older people owing to various economic or societal forces could alter older people's time-use and out-of-home activity patterns. Our study suggests that Hong Kong and other cities in the Asian region and beyond must aim at creating inclusive, age-friendly communities with adequate access to various activity opportunities in order to enhance quality of life in an aging society.